Miliarial type pseudolymphoma mimicking as granulomatous rosacea - Gharaei Nejad Kaveh; Rafiei Rana; Azimi Seyyede Zeinab; Rafiee Behnam (Our Dermatology Online, 2017)
Miliarial type lymphocytoma cutis is a rare type of psuedolymphoma which is described by numerous semi-translucent papules on the sun exposed regions. Herein, we present a 25-year-old woman with numerous permanent translucent tiny papules on the face. Microscopic examination revealed dense infiltration of lymphocytes in the reticular dermis with lymphoid follicle formation and significant B-cell lymphocytes in immunohistochemistry study. She was diagnosed as miliarial type pseudolymphoma and treated with topical momethasone furoate ointment and oral hydroxychloroquine with a good response.